Dietary and lifestyle determinants of the lifetime cardiovascular risk during early adulthood - Abulmeaty, Mahmoud M. A.; Almajwal, Ali M.; ElSadek, Mohamed Farouk; Aldisi, Dara; Al-Momani, Mohammed M.; Alquraishii, Mohamed; Razak, Suhail; Almadani, Najwa K.; Almutawa, Deema A. (Progress in Nutrition, 2019)
Background and aim: Dietary and lifestyle parameters were used frequently to understand the susceptibility to chronic diseases. The aim is to investigate the impact of some dietary and lifestyle determinants on the lifetime cardiovascular risk during the early adulthood. Methodology: A total of 371 subjects (163 men and 208 women) aged 18-46 years were enrolled in a cross-sectional study. Dietary and lifestyle data were collected by using the simple lifestyle indicator questionnaire. Fasting glucose and lipid panel were analyzed, in addition to anthropometric measurements and blood pressure recording in the sitting position. Lifelong American college of cardiology/American heart association (lifetime ASCVD) risk score was calculated depending on the published tool using the age, gender, systolic blood pressure, body mass index or total and HDL cholesterol, smoking status, presence of diabetes and presence or treatment for hypertension. Multiple logistic regression was used to test determinants of long-term cardiovascular risk score. Results: Those having non-optimal risk levels for lifetime ASCVD risk were 46.6% and 32.1% of men and women groups respectively. Among Saudi women, following a dietary guidelines and having no family history of cardiovascular disease reduces the risk of lifetime ASCVD by about 89% and 80% {odds ratio (95% confidence interval) = 0.11 (0.02-0.52) and 0.20 (0.05-0.82), respectively, p